“Too small to shine? Not really!”: Developing Society 5.0 adaptation initiatives for SMEs - Santos, C.; Ferreira, F.; Dabić, M.; Ferreira, N.; Ferreira, J. (IEEE Transactions on Engineering Management, 2024)
Society 5.0 is an extremely popular idea in current socioeconomic contexts. The transition process of evolving into this superintelligent society envisioned by the Japanese government is still ongoing, but this paradigm has already had an impact through recent changes in societies’ perspectives and ambitions. The academic contributions on this topic are still scarce, so further research is required particularly in the context of small- and medium-sized enterprises (SMEs). Society 5.0 encompasses various complex subjective aspects (i.e., variables) that require a constructivist approach to the associated decision-making processes. This study sought to overcome limitations identified in previous studies of Society 5.0’s varied dimensions by applying a combination of cognitive mapping and decision-making trial and evaluation laboratory techniques in a neutrosophic context. These methodologies provided a holistic perspective on the research topic, as well as identifying the most important variables to be included in the analysis system and defining their causal interrelationships. This comprehensive decision-support system was constructed by a panel of experts in related fields in order to mirror SME realities. The benefits and practical contributions of the proposed analysis system are discussed, and the results confirm that SMEs are not too small to shine in Society 5.0.